PENCIPTAAN PELUANG USAHA KULINER PINDANG IKAN PATIN SEBAGAI MAKANAN KHAS DAERAH PALEMBANG - Noer, Namira Imelia Ramadiena; Hertati, Lesi; Asharie, Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Pindang ikan patin is a typical food of the Palembang region that has been widely recognized as a superior product. This study aims to reveal the marketing strategies used by Micro, Small and Medium Enterprises (MSMEs) in increasing the superiority of pindang ikan patin in the area. This research method uses primary data obtained through interviews, observation, and documentation directly from the first source. The results showed that pindang tulang MSMEs in the Sukawinatan area implemented various marketing strategies, involving aspects of product, price, place of business, and promotion. Of the four strategies, the product marketing strategy has a significant influence, mainly due to the variation in product quality of pindang ikan patin, which includes pindang ikan patin, pindang tulang, and pindang ikan gabus. These products are known for their high quality. In addition, the price of pindang ikan patin products is relatively affordable and competitive in the market. MSMEs in Sukawinatan have successfully developed their product marketing by utilizing online media, particularly through the promotion of the place and types of pindang offered. This research provides a comprehensive overview of the marketing strategy practices implemented by bone pindang MSMEs in the Palembang area. By understanding the success of these marketing strategies, it can be concluded that a focus on product quality, competitive pricing, and utilization of online media are key factors in increasing the competitiveness and popularity of pindang ikan patin as a regional specialty.